Islets Transplantation at a Crossroads - Need for Urgent Regulatory Update in the United States: Perspective Presented During the Scientific Sessions 2021 at the American Diabetes Association Congress - Witkowski, Piotr; Philipson, Louis H.; Buse, John B.; Robertson, R. Paul; Alejandro, Rodolfo; Bellin, Melena D.; Kandeel, Fouad; Baidal, David; Gaglia, Jason L.; Posselt, Andrew M.; Anteby, Roi; Bachul, Piotr J.; et al. (Frontiers in Endocrinology, 2022)
Clinical islet allotransplantation has been successfully regulated as tissue/organ for transplantation in number of countries and is recognized as a safe and efficacious therapy for selected patients with type 1 diabetes mellitus. However, in the United States, the FDA considers pancreatic islets as a biologic drug, and islet transplantation has not yet shifted from the experimental to the clinical arena for last 20 years. In order to transplant islets, the FDA requires a valid Biological License Application (BLA) in place. The BLA process is costly and lengthy. However, despite the application of drug manufacturing technology and regulations, the final islet product sterility and potency cannot be confirmed, even when islets meet all the predetermined release criteria. Therefore, further regulation of islets as drugs is obsolete and will continue to hinder clinical application of islet transplantation in the US. The Organ Procurement and Transplantation Network together with the United Network for Organ Sharing have developed separately from the FDA and BLA regulatory framework for human organs under the Human Resources & Services Administration to assure safety and efficacy of transplantation. Based on similar biologic characteristics of islets and human organs, we propose inclusion of islets into the existing regulatory framework for organs for transplantation, along with continued FDA oversight for islet processing, as it is for other cell/tissue products exempt from BLA. This approach would reassure islet quality, efficacy and access for Americans with diabetes to this effective procedure.